EFFECTS OF CARRIED THROUGH EXERCISES OF FLEXIBILITY IN BODYBUILDING DEVICES, ON THE ARTICULAR AMPLITUDE OF MOVEMENT IN PRACTITIONERS OF RESISTED EXERCISE OF THE MASCULINE SEX (Fiep Bulletin - online, 2011)
The present study objectified to analyze the effect of exercises of passive flexibility on the articular amplitude of movement(AAM), in adults of the masculine sex, carried through in resisted training (RT) devices, using the method of passive flexibility. 20 masculine sex people got part on the study, divided in control groups (CG), formed by 10 men (23,6±2,6 years old) that hadn't been submitted to the flexibility training and to the experimental group (EG), forrmed by 10 masculine sex people ( 24,7 ±5,14 years old ), submitted , during 8 weeks of application of two repetitions of 10 seconds of insistence and from 20 to 25 seconds of break on the thorico-lumbar flexion exercises (TLF). Flexion of the Right and left Hip (LHF and RHF), Horizontal Extension of the Right and left Shoulder (HERS and HELS) and Left and Right backflexion  (LBF and RBF) in the devices of seated Rowed, Leg Press 45º, Converging Supino and vertical calf, respectively. For the mensuration of flexibility it was used the protocol of goniometry of the Laboratory of Biometry and physiology of Effort(LABIFIE), using Goniometric method. For statistics  analysis test “t” of Student and ANOVA One Way was used. Results: magnificent rises on the administration of the TLF exercises(p
Keywords: training; flexibility; devices; resisted exercise